2011
DOI: 10.1111/j.1365-3059.2010.02406.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and forest diseases

Abstract: As climate changes, the effects of forest diseases on forest ecosystems will change. We review knowledge of relationships between climate variables and several forest diseases, as well as current evidence of how climate, host and pathogen interactions are responding or might respond to climate change. Many forests can be managed to both adapt to climate change and minimize the undesirable effects of expected increases in tree mortality. We discuss four types of forest and disease management tactics -monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
421
0
17

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 618 publications
(439 citation statements)
references
References 100 publications
(184 reference statements)
1
421
0
17
Order By: Relevance
“…In such places, gradual changes in climate may cross thresholds that cause rapid changes in tree growth, as well as increased susceptibility to attack from insects and pathogens (Raffa et al 2008;Bentz et al 2010;Yan and Niu 2008;Ayres and Lombardero 2000;Sturrock et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In such places, gradual changes in climate may cross thresholds that cause rapid changes in tree growth, as well as increased susceptibility to attack from insects and pathogens (Raffa et al 2008;Bentz et al 2010;Yan and Niu 2008;Ayres and Lombardero 2000;Sturrock et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Rates of introduction are increasing (1), driven by changing climate (2) and altered patterns of travel and trade (3). Emerging epidemics cause direct economic loss from death and restricted growth of trees grown for timber and horticultural use (4).…”
mentioning
confidence: 99%
“…Climate change can alter susceptibility of trees to certain pathogens and change the geographical distribution of pathogens (Sturrock et al, 2011). Studying the impacts of rising CO 2 concentrations, Santos et al (2013) observed that at high air-CO 2 concentrations the plantlets of two eucalyptus clones had longer disease incubation period and lower severity of wilt caused by Ceratocystis fimbriata.…”
Section: Crescimento De Plantas E Severidade Da Mancha Foliar Em Eucamentioning
confidence: 99%